Women’s Experiences of Infertility: Self and Socially Constructed Identities - Basnet, Pramila; Khatiwada, Shambhu Prasad (Sotang, Yearly Peer Reviewed Journal, 2025)
Infertility is a significant issue affecting women's reproductive health and their personal and social identity formation. This paper explores the influence of social constructs on women's experiences of infertility-related identities. Using a phenomenological research design, the study engaged three women who have lived with infertility for over a decade. Data were collected through in-depth interviews and analyzed thematically. The finding indicates that infertility can cause significant emotional strain, including feelings of inadequacy, self-doubt, and social isolation. This paper revealed that there is a strong connection between womanhood and motherhood in Nepali society, with childless women often stigmatized as Banjhi, resulting in their marginalization. This paper concludes that infertility significantly affects women's identities, leading to increased emotional distress and isolation due to the disruption of social structures. This conclusion helps to advocate for societal attitudes towards infertile women, emphasizing that their identity should not be solely determined by their child-bearing capacity.